2016
DOI: 10.3201/eid2211.160141
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-ResistantCorynebacterium striatumAssociated with Increased Use of Parenteral Antimicrobial Drugs

Abstract: Device-related infections with this pathogen frequently require prolonged parenteral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 30 publications
7
43
0
2
Order By: Relevance
“…Corynebacterium striatum , a bacterium associated with infection and multi-drug resistance(G.J. et al, 2010; Hahn et al, 2016; Patel et al, 2016), was the most prevalent Corynebacterium spp. classified in DFU, with C. jeikeium, C. amycolatum, C. pseudogenitalium, C. tuberculostearicum , and C. resistens in lesser abundances (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corynebacterium striatum , a bacterium associated with infection and multi-drug resistance(G.J. et al, 2010; Hahn et al, 2016; Patel et al, 2016), was the most prevalent Corynebacterium spp. classified in DFU, with C. jeikeium, C. amycolatum, C. pseudogenitalium, C. tuberculostearicum , and C. resistens in lesser abundances (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…in DFU, detected in 28% of our specimens. Considered an emerging multi-drug resistant microbe(Hahn et al, 2016), C. striatum is an underrecognized cause of diabetic foot osteomyelitis(G.J. et al, 2010; Patel et al, 2016) suggesting it should not be classified as merely contaminating skin flora in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are more and more articles that report hard to treat infections due to nontoxigenic strains of Corynebacterium spp. with resistance to antibiotics [6,19,22].…”
Section: Introductionmentioning
confidence: 99%
“…Usually C. striatum shows excellent susceptibility to vancomycin. Hahn WO et al reported a total of 71% (n=121) of isolates resistant to penicillin, tetracycline, clindamycin, erythromycin and ciprofloxacin [15,16]. In the first case C. striatum that we isolated was susceptible to vancomycin and linezolid.…”
Section: Discussionmentioning
confidence: 72%
“…The bacteria is notorious for causing respiratory tract infections [14]. Multi drug resistant Cornyebacterium species are rapidly emerging [15,16]. Usually C. striatum shows excellent susceptibility to vancomycin.…”
Section: Discussionmentioning
confidence: 99%